The Rearticulation of Formal Sediments in Guimarães Rosas’s Literary Discourse - Sérgio Schaefer (Signo, 2017)
This article aims at analysing both the esthetical form and the rearticulation of its internal sediments as proposed by João Guimarães Rosa in his literary works. The analysis’ theoretical support is based on Theodor W. Adorno’s Teoria Estética. The broad objective of this study is to show that Rosa’s esthetical formalization is a call for changing. At the end of the article, a brief comparative study is made between Guimarães Rosa’s and Dostoievski’s calls for changing. Accordingly, some of the main issues of Bakthin’s theories about the works of the Russian writer will be reminded of and some of the main differences and similarities between Rosa’s and Dostoievski’s formal rearticulations will be pointed out.